Integrasi Varietas Tahan dan Bioinsektisida untuk Pengendalian Ulat Perusak Daun Kedelai - Indiati, Indiati; Bedjo, Bedjo (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Leaf-eating caterpillars are important soybean pests that widely distributed from tropical to sub-tropical regions under wet and humid conditions. In Indonesia, these caterpillars attacked 1,316 hectares of soybean crops in year 2002, and it increased to 2,902 hectares of soybean crops in year 2006. Therefore, the effective pest control needs to be identified. The experiment on controlling leaf eating caterpillars used bio-insecticides of NPV and SBM, and resistant varieties was conducted at Kendalpayak Experimental Farm of Indonesia Legumes and Tuber Crops Research Institute in dry season of 2016. A strip plot design with three replications was applied, where the vertical factor was varieties i.e. (1) Wilis, (2) Degra 1, and (3) G100H, and types of insecticide as horizontal factors i.e. (1) without insecticides, (2) 50 g of neem-seed flour (SBM) in 1 litre of water, (3) 2 g of SlNPV in 1 litre of water, (4) SBM + NPV, and (5) chemical insecticide. The results indicated that SlNPV was effectively suppressed the population of caterpillars as shown by its lowest numbers. Also, the combination treatment of SBM + NPV had better suppression than that of chemical insecticide. The role of Degra 1 variety, which is a resistant variety to leaf eating caterpillar, was very important in suppressing the damage rate of the plants as pointed out by 26% reduction of damage rate compared to that of Wilis variety (the susceptible variety to leaf eating caterpillars). The effectiveness of leaf eating caterpillars control could be enhanced by combining the resistant variety of Degra 1 with NPV bio-insecticide. This application obtained 35% of suppression rate which was equal to that obtained by the combination of the resistant variety of Degra 1 with chemical insecticide. It is therefore, the variety of Degra 1 has a huge opportunity to be developed in leaf eating caterpillarsâ endemic soybean areas.